Autoestima y calidad de vida en pacientes con cáncer de mama. - Lavalle Mayón, Kerlly Lizbeth (2025)
Breast cancer is one of the leading causes of morbidity and mortality, affecting not only physical health but also the emotional and social dimensions of patients' lives. This study aimed to characterize self-esteem and quality of life in patients diagnosed with breast cancer. A descriptive-level bibliographic review was conducted, gathering data from high-impact repositories such as PubMed, Web of Science, Scopus, and ProQuest. A total of 22 scientific articles published between 2015 and 2025 in Spanish, English, and Portuguese were selected. The Critical Review Form for Quantitative Studies (CRF-QS) was used for quality assessment. Findings revealed that self-esteem levels are influenced by clinical, individual, social, and cultural factors. Patients with high self-esteem tend to exhibit greater resilience, optimism, and positive coping strategies. Those with moderate self-esteem show fluctuating adaptation, balancing confidence with periods of insecurity. Conversely, low self-esteem is associated with heightened anxiety, depression, hopelessness, and poor disease management. Regarding quality of life, breast cancer significantly impacts various dimensions: physically (pain, fatigue, and treatment side effects), psychologically (anxiety, depression, and altered self-image), and socially (interpersonal relationships and daily participation). In conclusion, self-esteem plays a crucial role in patients' coping capacity, influencing their emotional well-being, resilience, and adjustment to illness. Enhancing self-esteem contributes to better quality of life and facilitates responses to the physical, emotional, and social demands of cancer treatment.